Shifting oxygen charge towards octahedral metal : a way to promote water oxidation on cobalt spinel oxides - Sun, Shengnan (2021)
Cobalt spinel oxides are a class of promising transition metal (TM) oxides for catalyzing oxygen evolution reaction (OER). Their catalytic activity depends on the electronic structure. In a spinel oxide lattice, each oxygen anion is shared amongst its four nearest transition metal cations, of which one is located within the tetrahedral interstices and the remaining three cations are in the octahedral interstices. This work uncovered the influence of oxygen anion charge distribution on the electronic structure of the redox-active building block Co-O. The charge of oxygen anion tends to shift toward the octahedral-occupied Co instead of tetrahedral-occupied Co, which hence produces strong orbital interaction between octahedral Co and O. Thus, the OER activity can be promoted by pushing more Co into the octahedral site or shifting the oxygen charge towards the redox-active metal center in CoOmetal-oxygen covalency octahedra.